The Impending Renaissance in Discovery & Development of Natural Products - V. Pawar, Sandip; C. H. Ho, Joe; D. Yadav, Ganapati; G. Yadav, Vikramaditya (Current Topics in Medicinal Chemistry, 2017)
Antibiotics are wonder drugs. Unfortunately, owing to overuse, antibiotic resistance is now a serious problem. Society now finds itself in the post-antibiotic era, and the threat of infectious diseases is on the rise. New antibiotics are sorely needed. There is strong evidence that suggests natural products are an attractive source of new antimicrobials. They posses desirable structural and chemical properties that make them potent thearpeutics. However, steep tehnological challenges associated with screening and manufacturing these molecules has stifled the discovery, development and marketing of new antimicrobials. To this end, two recent scientific developments are poised to redress this situation. The recent development of metagenomics and ancillary high-throughput screening technologies has exponentiated the volume of useful genetic sequence information that can be screened for antimicrobial discovery. These approaches have been instrumental in the discovery of new antibiotics from soil and marine environments. Secondly, a new manufacturing paradigm employing metabolic engineering as its engine has greatly accelerated the path to market for these molecules, in addition to improving the atom and energy economy of antimicrobial manufacturing. We outine these developments in this review, and provide a perspective on integrating next-generation approaches such as metagenomics and metabolic engineering with traditional methodologies for discovering and manufacturing antimicrobial natural products in order to unleash a rennaissance in the discovery and development of antimicrobials.
Keywords: Metabolic Engineering